Análise térmica e energética de uma edificação comercial visando conforto térmico e redução da demanda de energia elétrica - Roman, Leila Maria Tamanini (Universidade do Vale do Rio dos Sinos, 2013)
This study presents the energetic evaluation, through the software EnergyPlus, of an external room with acclimatization and of a seven-story building with natural ventilation. For this, the monthly energy consumed, the climatic data, the architectonic characteristics, the number of people, the location and other characteristics which can interfere directly or indirectly the room’s energy consumption were monitored. The data obtained through in loco survey, memorials of the infrastructure area and human resources, as well as the analysis of the monthly electrical energy bills, are considered as parameters for the simulation and they validate the results, allowing the search for new alternatives that aim at consumption efficiency and reduction. The evaluations are performed based on two buildings which are part of Centro Administrativo de Lojas Colombo, located in Farroupilha, Rio Grande do Sul, Brazil. The analysis aims at minimizing the electric energy consumption with the purpose of ensuring the maximum of comfort hours, so it evaluates the indexes of thermal comfort, the inside temperatures, the inside heat gains, the operation conditions of the air-conditioning in the outside room, and the necessary air-conditioning power for the installation in the fifteen thermal zones which belong to the building, verifying the energetic consumption of the used alternatives and the cost-benefit ratio. Through the simulations in the outside room, it was detected that with the use of thermally efficient material, the thermal exchanges between inside and outside are minimized, the same occurs with the substitution of old equipment, such as tube monitors. In the fifteen thermal zones of the building, the installation of an air-conditioning system is an alternative to improve the thermal comfort indexes in days with higher or lower temperatures. These are situations in which the natural ventilation is not enough to ensure that the environment is comfortable. The air conditioning simulated increased the building energy consumption in 17%, although a significative increase in thermal comfort was achieved. At the external room a 14% reduction in electricity consumption, over the total consumption, and the guarantee of 86% of occupied hours in comfort was obtained.
Keywords: EnergyPlus; Eficiência energética; Conforto térmico; Redução de consumo de energia; Energy efficiency; Thermal comfort; Reduction of energy consumption; ACCNPQ::Engenharias::Engenharia Mecânica